Intrahost Evolution of Methicillin-Resistant Staphylococcus aureus USA300 Among Individuals With Reoccurring Skin and Soft-Tissue Infections - Azarian, Taj; Daum, Robert S.; Petty, Lindsay A.; Steinbeck, Jenny L.; Yin, Zachary; Nolan, David; Boyle-Vavra, Susan; Hanage, W. P.; Salemi, Marco; David, Michael Z. (The Journal of infectious diseases, 2016)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) USA300 is the leading cause of MRSA infections in the United States and has caused an epidemic of skin and soft-tissue infections. Recurrent infections with USA300 MRSA are common, yet intrahost evolution during persistence on an individual has not been studied. This gap hinders the ability to clinically manage recurrent infections and reconstruct transmission networks. Methods. To characterize bacterial intrahost evolution, we examined the clinical courses of 4 subjects with 3–6 recurrent USA300 MRSA infections, using patient clinical data, including antibiotic exposure history, and whole-genome sequencing and phylogenetic analysis of all available MRSA isolates (n = 29). Results. Among sequential isolates, we found variability in diversity, accumulation of mutations, and mobile genetic elements. Selection for antimicrobial-resistant populations was observed through both an increase in the number of plasmids conferring multidrug resistance and strain replacement by a resistant population. Two of 4 subjects had strain replacement with a genetically distinct USA300 MRSA population. Discussions. During a 5-year period in 4 subjects, we identified development of antimicrobial resistance, intrahost evolution, and strain replacement among isolates from patients with recurrent MRSA infections. This calls into question the efficacy of decolonization to prevent recurrent infections and highlights the adaptive potential of USA300 and the need for effective sampling.